1983
DOI: 10.1073/pnas.80.9.2752
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II deficiency identified as the primary defect in the autosomal recessive syndrome of osteopetrosis with renal tubular acidosis and cerebral calcification.

Abstract: The clinical, radiological, and pathological findings in three siblings affected with the autosomal recessive syndrome of osteopetrosis with renal tubular acidosis and cerebral calcification have been reported. In an effort to explain the pleiotropic effects of the mutation producing this disorder, we postulated a defect in carbonic anhydrase H (CA II), the only one of the three soluble isozymes of carbonic anhydrase that is.known to be synthesized in kidney and brain. We report here biochemical and immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
275
0
3

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 523 publications
(282 citation statements)
references
References 41 publications
4
275
0
3
Order By: Relevance
“…CAII regulates cellular pH, CO 2 , and HCO 3 -transport, and maintains H 2 O and electrolyte balance by reversible hydration of CO 2 . CAII affects synaptic remodeling, consistent with the notion that a deficiency of CAII leads to cognitive defects varying from disabilities to severe mental retardation, suggesting the importance of CAII in cognitive function (351). Though levels of CAII are elevated, CAII activity is diminished in the AD brain (271), likely caused by the oxidative modification of the enzyme.…”
Section: Identification Of Carbonylated Proteins In Brainsupporting
confidence: 53%
“…CAII regulates cellular pH, CO 2 , and HCO 3 -transport, and maintains H 2 O and electrolyte balance by reversible hydration of CO 2 . CAII affects synaptic remodeling, consistent with the notion that a deficiency of CAII leads to cognitive defects varying from disabilities to severe mental retardation, suggesting the importance of CAII in cognitive function (351). Though levels of CAII are elevated, CAII activity is diminished in the AD brain (271), likely caused by the oxidative modification of the enzyme.…”
Section: Identification Of Carbonylated Proteins In Brainsupporting
confidence: 53%
“…CA catalyzes CO 2 hydration and the reverse reaction between H ϩ and HCO 3 Ϫ ions, which helps in the maintenance of intracellular pH (66,67). CA II deficiency in humans is an autosomal recessive disease characterized by renal tubular acidosis, osteopetrosis, cerebral calcification, and growth retardation (68,69). However, previous studies reported that CA II promotes cardiomyocyte hypertrophy and its inhibition reverts hypertrophy (70,71).…”
Section: D-dige Spotmentioning
confidence: 99%
“…[3][4][5] Other involved genes include isolated reports of rare mutations in the gray lethal gene, 6 as well as abnormalities in the carbonic anhydrase II gene. 7 The deposition of bone by osteoblasts without resorption by osteoclasts results in marked increase in bone density and causes encroachment of bone marrow space resulting in progressive marrow failure and compensatory extramedullary hematopoiesis. 8,9 Compression of cranial nerves leads to neurological deficits, particularly blindness, that may occur early in life.…”
Section: Introductionmentioning
confidence: 99%